KONSEP PENDEKATAN STEM DALAM PEMBELAJARAN MATEMATIKA PADA SISWA SEKOLAH DASAR - Supriyanto; Nurhaningtyas Agustin (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
In the 21st century, several abilities needed to deal with development. In learning mathematics, mathematical literacy skills are vital requirements nowadays. Because with mathematical literacy skills we can analyze, reason, and communicate ideas effectively when formulating, solving, and interpreting problems mathematically in various situations in real life. So it is important to teach mathematical literacy skills from the primary education. The use of the STEM approach in learning mathematics can be used to improve mathematical literacy skills. Because the STEM approach integrates several disciplines including science, engineering, engineering and mathematics. In this article compiled using Library Research, the collected literacy was extracted from relevant journal article sources. The data collection procedure uses the documentation method, the data that has been collected will then be analyzed using data reduction techniques, content analysis, and drawing conclusions. Obtained STEM is an integration of learning from various disciplines. Core competencies that can be trained with STEM include problem solving, innovation and creativity, communication, critical thinking, metacognition, self-regulation and discipline. STEM-based mathematics learning can be designed by determining subject titles, subject descriptions, objectives, prerequisite knowledge, linking with technical materials, lists of learning resources and tools and materials.